Behind Covid-19: Panic Buying, Service Convenience in Modern Market Indonesia - Dinda Syachadi, Nourissa; Christy Avega Dumatri, Agatha; Wahyudi Rahman, Muhammad Fajar; Fazlurrahman, Hujjatullah (SEISENSE Journal of Management, 2021)
Purpose- This study aims to analyze the effect of panic buying and service convenience on consumer purchasing decisions in modern markets such as mini markets, supermarkets, and hypermarkets in Surabaya. Design/Methodology- This research makes use of a quantitative approach. The object of this research is consumers who shop at grocery stores during the Covid-19 pandemic between March and June 2020 in the city of Surabaya, East Java, Indonesia. Within this research, 84 respondents were used as the sample. The process of collecting the data was conducted through online-based questionnaires. Multiple linear regression analysis with the help of SPSS 23.0 software was used to analyze the research. Findings- The researchers concluded that all existing hypotheses both H1 and H2, were valid. It also showed a significant positive relationship between panic buying, service convenience, and consumer purchasing decision behavior. Practical Implications- Furthermore, the results stated that the modern market must understand the community's conditions and keep up with the latest situation surrounding customers’ needs.